THE EFFECT OF HA-COATED Mg ZK60 SCREWS ON CARDIOVASCULAR FUNCTION IN EXPERIMENTAL ANIMALS - Le Van Hai; Le Hanh (Tạp chí Y học Quân sự, 2026)
Objective: To evaluate the effects of hydroxyapatite (HA)-coated Mg ZK60 screws on cardiovascular function when implanted into the femurs of experimental animals. Materials and methods: A prospective, experimental cross-sectional study was conducted on 84 healthy white rabbits, randomly divided into 3 groups (Group 1: 28 rabbits implanted with HA-coated Mg ZK60 screws; Group 2: 28 rabbits implanted with uncoated Mg ZK60 screws; Group 3: 28 rabbits implanted with titanium screws). Cardiovascular function was assessed via heart rate, P-wave duration and amplitude, R-wave amplitude, QRS complex duration, and T-wave amplitude before surgery and at 3, 7, 30, 60, 90, and 180 days postoperatively. The study was carried out at the Department of Pathophysiology, Military Medical Academy. Results: There were no statistically significant differences in heart rate, P-wave duration and amplitude, R-wave amplitude, QRS duration, and T-wave amplitude before and after implant surgery, as well as between the groups at each follow-up time point (p > 0.05). Conclusion: HA-coated Mg ZK60 screws and the control screw groups do not affect the cardiovascular function of experimental rabbits when implanted into their femurs.